2020
DOI: 10.1186/s13287-020-1577-2
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted characterization of the signatures and efficacy of mesenchymal stem/stromal cells in acquired aplastic anemia

Abstract: Background: Longitudinal studies have verified the pivotal role of mesenchymal stem/stromal cells (MSCs) in the bone marrow microenvironment for hematopoiesis and coordinate contribution to leukemia pathogenesis. However, the precise characteristics and alternation of MSCs during acquired aplastic anemia (AA) remain obscure. Methods: In this study, we originally collected samples from both healthy donors (HD) and AA patients to dissect the hematological changes. To systematically evaluate the biological defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(108 citation statements)
references
References 31 publications
1
103
0
Order By: Relevance
“…hUC-MSCs were co-cultured with CD4 + T cells at a ratio of 1:10 as we described before. 2,21 For Th cell analysis, 100 ng/mL Phorbol-12myristate-13-acetate (PMA) (Sigma),1 μg/mL Ionomycin (Sigma) and 2 μmol/L monensin (BD Biosciences) were used to stimulate T cells.…”
Section: Co-culture Of Lymphocytes With Huc-mscsmentioning
confidence: 99%
“…hUC-MSCs were co-cultured with CD4 + T cells at a ratio of 1:10 as we described before. 2,21 For Th cell analysis, 100 ng/mL Phorbol-12myristate-13-acetate (PMA) (Sigma),1 μg/mL Ionomycin (Sigma) and 2 μmol/L monensin (BD Biosciences) were used to stimulate T cells.…”
Section: Co-culture Of Lymphocytes With Huc-mscsmentioning
confidence: 99%
“…Since the 1960s, MSCs were initially isolated from bone marrow followed by various adult tissues (e.g., adipose tissue and dental pulp) and perinatal tissues (e.g., umbilical cord and placenta), as well as human pluripotent stem cells (e.g., hESCs, iPSCs) (20,(42)(43)(44). Of the aforementioned MSCs, hBM-MSCs and hUC-MSCs are associated with the most applications and long-term in vitro proliferation capacity, respectively (20,24). For decades, the authors of the present study, as well as others, have reported the clinical and preclinical applicability of MSCs in refractory and recurrent diseases, such as Crohn's disease, aplastic anemia, acute myocardial infarction, GVHD and even H5N1-infected pneumonia which cause acute lung injury and acute respiratory distress syndrome (ALI/ARDS), which are similar to the symptoms of SARS-CoV-2 infection (20,24,25,42,43,45).…”
Section: Discussionmentioning
confidence: 99%
“…Of the aforementioned MSCs, hBM-MSCs and hUC-MSCs are associated with the most applications and long-term in vitro proliferation capacity, respectively (20,24). For decades, the authors of the present study, as well as others, have reported the clinical and preclinical applicability of MSCs in refractory and recurrent diseases, such as Crohn's disease, aplastic anemia, acute myocardial infarction, GVHD and even H5N1-infected pneumonia which cause acute lung injury and acute respiratory distress syndrome (ALI/ARDS), which are similar to the symptoms of SARS-CoV-2 infection (20,24,25,42,43,45). Very recently, Leng et al and Wang et al reported the clinical remission of a 65-year-old female critically ill patient with COVID-19 with hUC-MSC transplantation for 3 times as well, whereas the lung damage was relatively mild, which was confirmed by another studies (14,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations